Remission of type 2 diabetes mellitus through intensive lifestyle modification in ambulatory setting - Annu Antony; Priyamadhaba Behera; Binod Kumar Patro; Manish Taywade (Indian Journal of Community and Family Medicine)
Type 2 diabetes mellitus (T2DM) is a widespread chronic condition often influenced by a complex interplay of factors. We present a remarkable case of a 54-year-old man diagnosed with T2DM in February 2016, whose journey sheds light on the potential for T2DM remission through lifestyle modifications. Remarkably, at the time of diagnosis, he displayed elevated glycated hemoglobin (HbA1c) levels at 11.6% alongside extreme work-related stress, as evidenced by a Depression Anxiety Stress Scale (DASS) score of 27. Following a structured treatment plan, including pharmacological therapy and lifestyle changes, the patient demonstrated good glycemic control over 2 years. However, what makes this case truly exceptional is his decision to discontinue all medications against medical advice in October 2018. In this period, he continued to focus on lifestyle adjustments, including exercise, diet, and addressing the root cause of his stress. Crucially, the patient’s commitment to stress management and lifestyle modifications had a profound impact on his health. Through meticulous cross-verified testing at the All India Institute of Medical Science, Bhubaneswar, this case reveals substantial improvements in HbA1c levels, from 11.6% to 5.3% and a significant reduction in stress levels (DASS score from 27 to 12). Corresponding reductions were also observed in fasting blood sugar and postprandial blood sugar levels. Furthermore, microalbuminuria, a complication associated with diabetes, exhibited signs of reversal. These findings suggest that T2DM and its associated complications can be effectively managed and even reversed in certain cases through lifestyle modifications, underscoring the intricate link between mental well-being and physiological outcomes.